2011
DOI: 10.1007/s12070-011-0365-9
|View full text |Cite
|
Sign up to set email alerts
|

A Cross Sectional Study of Oral Submucous Fibrosis in Central India and the Effect of Local Triamcinolone Therapy

Abstract: The use of processed arecanut is on the increase. In the impending danger of increased occurrence of oral submucous fibrosis and subsequent oral cancer following this habit is colossal. So an attempt is made to clinically evaluate the condition and to evaluate the effect of triamcinolone on this condition. Using the clinical data collected from the patients presenting in the ENT OPD of NSCB Medical College Hospital, Jabalpur, a cross sectional study was done and the effect of intralesional triamcinolone on thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…The pathogenesis of OSF is complex and still not fully understood. The results of medical and physical therapies for OSF management are shown in Table 3 [28][29][30][31][32][33][34][35] and those of representative surgical therapies are summarized in Table 4. [36][37][38][39][40]…”
Section: Tre Atmentmentioning
confidence: 99%
See 1 more Smart Citation
“…The pathogenesis of OSF is complex and still not fully understood. The results of medical and physical therapies for OSF management are shown in Table 3 [28][29][30][31][32][33][34][35] and those of representative surgical therapies are summarized in Table 4. [36][37][38][39][40]…”
Section: Tre Atmentmentioning
confidence: 99%
“…For the disease at the intermediate or advanced stage, physical and/or surgical therapies are necessary for alleviating symptoms of pain of oral mucosa and for increasing mouth opening. The results of medical and physical therapies for OSF management are shown in Table and those of representative surgical therapies are summarized in Table …”
Section: Treatmentmentioning
confidence: 99%
“…In study done by Ameer and others, significant improvement in mouth opening is observed following local triamcinolone injection therapy. 13 Out of 50 patients in this study, treated 21 (42%) patients showed increase in mouth opening of greater than 11 mm and 19 (38%) patients showed an increase of 6-10 mm and the rest patients showed an increase of less than 5 mm.…”
Section: Discussionmentioning
confidence: 62%
“…Some clinicians also advise the use of intralesional injections with steroids to improve mouth opening of the patient. In a study conducted by (Ameer and Shukla, 2012;Ajay et al, 2017) it was observed that intralesional injections with triamcinolone in OSMF patients by giving biweekly submucosal injections of 40 mg triamcinolone for 12 weeks, patients subjectively showed improvement in symptoms and objectively increase in mouth opening was observed. However, such modalities have drawbacks too.…”
Section: Resultsmentioning
confidence: 99%